Quantification of Natural CO2 Emission Through Faults and Fracture Zones in Coal Basins. Issue 7 (30th March 2021) - Ma, Y.; Kong, X.‐Z.; Zhang, C.; Scheuermann, A.; Bringemeier, D.; Li, L.
Abstract: With the presence of highly permeable pathways, such as faults and fractures zones, coal seam gases, particularly CO2, could potentially migrate upwardly from the coal deposits into the shallow subsurface and then to the atmosphere. This letter reports soil gas mapping and gamma ray survey in coal basin of Hunter River Valley, Australia. The survey facilitated the delineation of fault structures across the sampling regions, where the identified faults were confirmed by an independent drilling investigation later. Furthermore, to evaluate the gas emission fluxes from coalbeds through fault zones, the measured CO2 concentrations, coupled with an inverse modeling, enable the estimation of the width of the fault zone and associated CO2 emission flux in the range of 2 × 10 −5 –6 × 10 −5  mol/m 2 /s at the study site. Our new approach provides a way to determine emissions of gases from deep formations, which may contribute considerably to the greenhouse gases cycles. Plain Language Summary: Australia is one of the world's biggest coal exporters. Total fugitive emissions in Australia have increased in line with the expanding coal and gas production sector. CO2 emissions may occur during the operation and following the closure of coal mines and coal seam gas fields. Leakage of gases to the atmosphere may be induced through fractured gas‐bearing strata and open vents. Hence, the emissions of CO2 from coal basins should be counted toward the overall emissions budget. The new approach proposed by the current study can be applied to estimate emissions of CO2 from fracture and fault zones, which have not been well quantified and yet can be potentially an important source of greenhouse gases contributing to the overall budget at a global scale. So this work could provide a better track progress on international emission commitments. Key Points: Field assessments on gas emission fluxes from coal basin at fault zones in the Hunter River Valley, Australia Soil gas mapping and gamma ray survey delineated several fault structures across the sampling transects, which were later confirmed by an independent borehole drilling investigation An inverse modeling is applied to determine the width of the fault zone and its CO2 emission flux at the study site